PERNIKAHAN BEDA AGAMA DI INDONESIA DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - Annisa Annisa (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT Marriage is the bond of sacred promises between men and women who love each other and should not be separated by anything except by death, an eternal marriage of course must be based on love, but the fact that there are often conflicts in the implementation of marriage because it is blocked by religion or different beliefs between a bride and groom, if viewed from the perspective of human rights, where the right to choose a partner should not distinguish between ethnicity, race, religion or class, because the right to choose a life companion is the personal right of every human being who there is, and that right should not be in conflict with regulations prohibiting interfaith marriages in Indonesia Keywords: Marriage